Fully implantable batteryless soft platforms with printed nanomaterial-based arterial stiffness sensors for wireless continuous monitoring of restenosis in real time. (October 2022) - Herbert, Robert; Elsisy, Moataz; Rigo, Bruno; Lim, Hyo-Ryoung; Kim, Hyeonseok; Choi, Chanyeong; Kim, Seungil; Ye, Sang-Ho; Wagner, William R.; Chun, Youngjae; Yeo, Woon-Hong
Abstract: Atherosclerosis is a common cause of coronary artery disease and a significant factor in broader cardiovascular diseases, the leading cause of death. While implantation of a stent is a prevalent treatment of coronary artery disease, a frequent complication is restenosis, where the stented artery narrows and stiffens. Although early detection of restenosis can be achieved by continuous monitoring, no available device offers such capability without surgeries. Here, we report a fully implantable soft electronic system without batteries and circuits, which still enables continuous wireless monitoring of restenosis in real-time with a set of nanomembrane strain sensors in an electronic stent. The low-profile system requires minimal invasive implantation to deploy the sensors into a blood vessel through catheterization. The entirely printed, nanomaterial-based set of soft membrane strain sensors utilizes a sliding mechanism to offer enhanced sensitivity and detection of low strain while unobtrusively integrating with an inductive stent for passive wireless sensing. The performance of the soft sensor platform is demonstrated by wireless monitoring of restenosis in an artery model and an ex-vivo study in a coronary artery of ovine hearts. The capacitive sensor-based artery implantation system offers unique advantages in wireless, real-time monitoring of stent treatments and arterial health for cardiovascular disease. Graphical Abstract: ga1 Highlights: Aerosol jet printing of nanomaterials and microfabrication for implantable system. Development of highly sensitive, soft capacitive strain sensor. Integrated wireless stent and sensor for sensing of arterial stiffness. Demonstration of wireless, real-time monitoring of restenosis.